PERSEPSI KOMPETENSI GURU, MOTIVASI BERPRESTASI DAN PRESTASI BELAJAR SEJARAH REGULASI DIRI SEBAGAI MEDIATOR PADA SISWA KELAS XI SMA PENGASIH - suhartana, suhartana (Jurnal Psikologi Terapan dan Pendidikan, 2013)
ABSTRACT This research is intended to examine the relationship of teacherâs competence, achievement motivation and self-regulation as the mediator to the students of SMA 1 Pengasih Kulon Progo Yogyakarta. This research is as the survey research using correlational quantitative approach. The Population of this research is students of class XI SMA 1 Pengasih Kulon Progo Yogyakarta, amount to 152 students. Research analyze used structural equation modelling (SEM), and it is found that self-regulation significantly mediate teacherâs competence perception showed by Î² = 0,297, pË0,1, and achievement motivation showed by Î² = 2,532 toward the history learning achievement to the student of class XI SMA 1 Pengasih Kulon Progo. The significant relation indicates that the strength of the teacherâs competence perception and achievement motivation with self-regulation as the mediator. Key word: Teacherâs competence perception, achievement motivation, self- regulation, history learning achievement